LIFE CYCLE ASSESSMENT (LCA) PENGOLAHAN SAMPAH PROSES TERMAL PADA TEMPAT PEMROSESAN AKHIR (TPA) SUPIT URANG KOTA MALANG - Dewa Indra luqmana Budiono; Naniek Ratni JAR (EnviroUS, 2021)
Malang City has an increasing population every year, causing the amount of waste generated by residents and public facilities to increase. The waste is transported to the Supit Urang final waste processing site (TPA) located in Sukun District, Malang City. Currently, processing is still using the controlled landfill method so that a large area is needed for the landfill process. TPA waste generation data collection by load count analysis method. Analysis of environmental aspects was carried out using the Life Cycle Assessment method, the input and output processes used SimaPro v.9.0.0.47 software. In the analysis of technical aspects and environmental analysis, a projection of waste generation to the Supit Urang TPA is required, namely 189,989 tons / year in 2030. From the results of the analysis of technical aspects, it is concluded that the thermal treatment of mixed waste incineration is the best because it only requires a small amount of land, namely 1,385m2. , using 1 reactor and 14 workers. For the type of waste composition that produces the smallest emissions is the type of organic waste biowaste. The results of the environmental impact analysis of biowaste organic waste gasification processing are Global Warming 4,51E8 kg CO2 eq, Ozone layer depletion 1,74E3 CFC-11 eq, Photochemical oxidation 1,11E5 C2H4 eq, Acidification 2,21E6 kg SO2 eq, Eutrophication 3, 03E6 PO4 eq